TEACHER’S FEEDBACK ON WRITING PROCEDURE TEXT - Yeni Erlita (BAHAS, 2021)
Abstract          This study is to investigate the types of teacher’s feedback on writing which given by the teacher’s and to find out how the teachers gave feedback on writing procedure text on junior high school, to elaborate the reasons of the teacher conducting the feedback on students writing of junior high school. It is used descriptive qualitative method. The findings were two types of feedback found on students’ writing procedure text students of junior school. They were: Direct and Indirect. Direct feedback which is provided in the 37 of the total feedback and has percentage as many as 79%. Second, it was indirect feedback, it has many percentages 21% of 10 the total feedback. And the teacher used those types of feedback on students’ writing was because it could make the students’ have more vocabularies and the students did not think more about what was the correct words. Keywords: Teachers’ feedback, students, procedure text, writing.